The Students’ Perceptions of Using Pictures Series and Video in Learning Narrative Text: A Questionnaire-Based Survey - Iinaas Maahiroh Al Mufiidah; Indri Astutik; Kristi Nuraini (International Journal of Science and Society, 2026)
Writing is one of the fundamental language skills in English language learning, particularly for junior high school students, because it enables learners to express ideas, organize information, and produce various types of texts such as narrative, descriptive, recount, report, analytical exposition, hortatory exposition, and news item texts. In learning narrative texts, many students experience difficulties in understanding story structures, developing vocabulary, organizing ideas coherently, and maintaining motivation during classroom activities. Therefore, the integration of engaging instructional media, such as pictures series and videos, has become increasingly important to facilitate students' comprehension and participation in English learning. This study aims to investigate students' perceptions of using pictures series and video in learning the narrative text Beauty and the Beast. Specifically, it explores students' views regarding the effectiveness of these media in improving vocabulary acquisition, story comprehension, motivation, classroom engagement, idea organization, and the ability to retell narrative texts. This study employed a quantitative questionnaire-based survey design involving 51 eighth-grade students from classes 8A and 8D at SMP Al Furqan Jember. The participants were selected using purposive sampling. Data were collected through 12-item Questionnaire Based Survey using a four-point Likert scale consisting of Strongly Agree, Agree, Disagree, and Strongly Disagree. The collected data were analyzed using descriptive statistics, including frequencies, percentages, mean scores, and standard deviations, to describe students' overall perceptions toward the implementation of pictures series and video in English learning. The findings revealed that most students demonstrated positive perceptions toward the use of pictures series and video. They reported that these instructional media helped them learn new vocabulary, understand the storyline more clearly, organize ideas systematically, remain focused during lessons, participate more actively in classroom activities, and enjoy learning English. Furthermore, students perceived that the combination of visual and audiovisual media created a more meaningful and engaging learning environment, which supported their understanding of narrative texts and encouraged greater confidence in retelling stories. These findings suggest that integrating pictures series and video can serve as an effective instructional strategy to enhance students' learning experiences and foster positive attitudes toward English language learning, particularly in narrative text instruction.